1969
DOI: 10.1159/000130023
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of XX cells in the testes of heterosexual bovine twins with XX/XY chimerism

Abstract: In five heterosexual male bovine twins and three freemartins, all not older than three months, XX/XY chimerism in the blood and gonads has been found. One heterosexual male bovine triplet showed at the age of 18 or 22 months XX/XY chimerism in the blood but not in the testes. In another male co-twin of a freemartin, XX/XY chimerism has been detected in the blood and the testes (at biopsy) at the age of two months. In the same animal, the blood chimerism was still present at the age of 18 months, whereas the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1970
1970
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Ohno et aL (1962) reported XX as well as XY chromosome-bearing cells in the testes of 1-day-old Holstein heterosexual twin bull calves. The presence of XX cells in testes of older affected bulls was reported by Teplitz et al (1967), Weiss and Hoffman (1969) and Lodja (1972), hut Weiss and Hoffmann (1969) reported that the ratio of XX to XY cells declined with advancing age. Whether XX cells are capable of meiotic division in the testicular environment of the heterosexual twin bull is a subject of controversy.…”
Section: Xx/xy Chimaeric Bullsmentioning
confidence: 54%
See 1 more Smart Citation
“…Ohno et aL (1962) reported XX as well as XY chromosome-bearing cells in the testes of 1-day-old Holstein heterosexual twin bull calves. The presence of XX cells in testes of older affected bulls was reported by Teplitz et al (1967), Weiss and Hoffman (1969) and Lodja (1972), hut Weiss and Hoffmann (1969) reported that the ratio of XX to XY cells declined with advancing age. Whether XX cells are capable of meiotic division in the testicular environment of the heterosexual twin bull is a subject of controversy.…”
Section: Xx/xy Chimaeric Bullsmentioning
confidence: 54%
“…There is some tendency for a positive association of ratio of XX to XY cells across tissues (Ohno et al, 1962;Teplitz et al, 1967;Dunn et al, 1968). For leucocytes and lymphocytes, the ratio of XX to XY cells also is repeatable across time (Teplitz et aL, 1967;Weiss and Hoffmann, 1969).…”
Section: Xx/xy Chimaeric Bullsmentioning
confidence: 99%
“…However, these observations have not been confirmed in the more recent studies by Dunn, Kenney, Stone & Bendel (1968) and Evans, West & Ford (personal communication) who were not able to discover either mitotic or meiotic X X metaphase plates in the testes of bulls born from heterosexual pregnancies. Weiss & Hoffmann (1969) described recently chimerism of leukocytes and of the gonadal tissue in several pairs of unlike-sexed bovine twins. However, in view of the fact that chimerism of the gonads was assessed on the basis of examination of cells grown in tissue cultures, the opinion of the present author, contrary to that of Weiss & Hoffmann, is that these findings provide evidence for chimerism of the somatic tissue rather than of the germinal tissue.…”
Section: Chimeras Composed Of Cells Of Dissimilar Genetic Sexmentioning
confidence: 99%